Real-time monitoring of Pseudomonas aeruginosa biofilm formation on endotracheal tubes in vitro - Pericolini, Eva; Colombari, Bruna; Ferretti, Gianmarco; Iseppi, Ramona; Ardizzoni, Andrea; Girardis, Massimo; Sala, Arianna; Peppoloni, Samuele; Blasi, Elisabetta (BMC microbiology, 2018)
Pseudomonas aeruginosa is an opportunistic bacterial pathogen responsible for both acute and chronic infections in humans. In particular, its ability to form biofilm, on biotic and abiotic surfaces, makes it particularly resistant to host's immune defenses and current antibiotic therapies as well. Innovative antimicrobial materials, like hydrogel, silver salts or nanoparticles have been used to cover new generation catheters with promising results. Nevertheless, biofilm remains a major health problem. For instance, biofilm produced onto endotracheal tubes (ETT) of ventilated patients plays a relevant role in the onset of ventilation-associated pneumonia. Most of our knowledge on Pseudomonas aeruginosa biofilm derives from in vitro studies carried out on abiotic surfaces, such as polystyrene microplates or plastic materials used for ETT manufacturing. However, these approaches often provide underestimated results since other parameters, in addition to bacterial features (i.e. shape and material composition of ETT) might strongly influence biofilm formation. We used an already established biofilm development assay on medically-relevant foreign devices (CVC catheters) by a stably transformed bioluminescent (BLI)-Pseudomonas aeruginosa strain, in order to follow up biofilm formation on ETT by bioluminescence detection. Our results demonstrated that it is possible: i) to monitor BLI-Pseudomonas aeruginosa biofilm development on ETT pieces in real-time, ii) to evaluate the three-dimensional structure of biofilm directly on ETT, iii) to assess metabolic behavior and the production of microbial virulence traits of bacteria embedded on ETT-biofilm. Overall, we were able to standardize a rapid and easy-to-perform in vitro model for real-time monitoring Pseudomonas aeruginosa biofilm formation directly onto ETT pieces, taking into account not only microbial factors, but also ETT shape and material. Our study provides a rapid method for future screening and validation of novel antimicrobial drugs as well as for the evaluation of novel biomaterials employed in the production of new classes of ETT.